2014
DOI: 10.1007/s10980-014-0144-6
|View full text |Cite
|
Sign up to set email alerts
|

Historical Northern spotted owl habitat and old-growth dry forests maintained by mixed-severity wildfires

Abstract: Context Reconstructing historical habitat could help reverse declining animal populations, but detailed, spatially comprehensive data are rare. For example, habitat for the federally threatened Northern spotted owl (NSO; Strix occidentalis caurina) was thought historically rare because low-severity fires kept forests open and habitat restricted to fire refugia, but spatial historical data are lacking. Objectives Here I use public land-surveys to spatially reconstruct NSO habitat and old-growth forests in dry f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 30 publications
0
33
0
Order By: Relevance
“…Hanson et al (2009Hanson et al ( , 2010, Baker (2012), Williams and Baker (2012), Dellasala and Hanson (2015), Odion et al (2014), and Baker (2015) have argued against fuels reduction or landscape restoration of any magnitude in Inland West pine and mixedconifer forests. They provide evidence that current large patches of high-severity fire may be within the historical range of variability for these forests, and the risk of loss of dense multistoried forest to high-severity fire is relatively low.…”
Section: Management Challenges In Msforestsmentioning
confidence: 99%
“…Hanson et al (2009Hanson et al ( , 2010, Baker (2012), Williams and Baker (2012), Dellasala and Hanson (2015), Odion et al (2014), and Baker (2015) have argued against fuels reduction or landscape restoration of any magnitude in Inland West pine and mixedconifer forests. They provide evidence that current large patches of high-severity fire may be within the historical range of variability for these forests, and the risk of loss of dense multistoried forest to high-severity fire is relatively low.…”
Section: Management Challenges In Msforestsmentioning
confidence: 99%
“…Notably, burned forests successionally link complex early seral forests [10,11] to future old-forest development [92] and are not ecological disasters as often claimed. Depending on fire severity, burned forests provide nesting and roosting (low-moderate severity) or foraging (high severity) habitat for spotted owls [45,46,51]. Federal managers, however, have increasingly proposed massive post-fire logging projects that degrade complex early seral forests [95] and spotted owl habitat [45,46], and that can elevate fuel hazards and re-burn potential [96,97].…”
Section: Discussionmentioning
confidence: 99%
“…In the dry portions of the owls' range, where fire is common, owl fitness is associated with a mosaic of older forests (nesting and roosting habitat) and open vegetation patches (foraging areas; [47,48]). Such patch mosaics are produced by mixed-severity fires characteristic of the Klamath and eastern Cascade dry ecoprovinces [49,50] that may have contributed to maintenance of owl habitat historically [51]. However, if fire increases in severity or homogeneity of burn patterns due to climate change [52,53] and if LSOG losses outpace recruitment rates over time, the beneficial habitat effects of fire to owls would diminish.…”
Section: Northern Spotted Owl Decline Slowed But Not Reversedmentioning
confidence: 99%
“…It is unclear what the proportion of this type of structure would have been under the historical disturbance regime. However, it probably was quite high, e.g., > 75%, given the recent historical work of Hagmann et al (2014) and Merschel et al (2014) and that of Baker (2015), who found that > 76% of the forests of all levels of canopy cover contained trees > 53 cm dbh in central Oregon. An earlier simulation study by Kennedy and Wimberly (2009) estimated that under historical regimes, 35% of all forest types on the Deschutes River, Oregon was covered by old forest structure, of which approximately 25% was in closed canopy conditions.…”
Section: Discussionmentioning
confidence: 99%